Applications of Savings and Deposit Contracts in Islamic Financial Institutions - Ghozali, Mohammad; Mafaza, Syofi Aruni (University of Darusssalam Gontor, 2020)
Wadi’ah is one of the forms of contract in Islamic financial institutions. Wadi’ah is the storage of goods accompanied by an agreement between the owner of the property or goods and a trusted party to take care of the property or goods. In principle, wadi’ah is to help the custodian of property or goods and the party in charge of the property or goods is as an assistant. Therefore, this wadi’ah contract is trust. This research study used a descriptive qualitative method with previous literature. The results of this study according to the type of wadi'ah are divided into two: namely the first is wadi'ah yad amanah (trust), where a person who receives a deposit is not allowed to use the goods or assets until it is taken back by the person who owns the property. The second type is wadi'ah yad dhamanah (guaranteed savings), which means that assets or goods can be used by the recipient of the deposit as long as they have not been returned to the depositor. However, if the profit is obtained from the utilization, then all of them are entitled to the recipient of the deposit. The status of the contract change from wadi'ah yad amanah to wadi'ah yad dhamanah can occur if: first, the assets in the deposit have been mixe. Second, recipients use the assets deposited. And third, recipients charge a service fee from the depositor.